Prototyping Efficient Desktop-as-a-Service for FPGA Based Cloud Computing Architecture - Shu, Shi; Shen, Xiang; Zhu, Yongxin; Huang, Tian; Yan, Shunqing; Li, Shiming (2012 IEEE Fifth International Conference on Cloud Computing, 2012)
Cloud computing, a delivery of computing as a service mainly implying how to use utilities in our context, can be provided either at infrastructure, platform or software levels. The Desktop-as-a-Service (DaaS) paradigm, derives from the software level Software-as-a-Service (SaaS) paradigm, is drawing increasing interest because of its transformation from desktops into a cost-efficient, scalable and comfortable subscription service. Unlike most existing solutions delivering service with various protocols based on image transmitting in PC dominating environment, we present a DaaS with cloud server technologies on FPGA to address the problem of high power consumption and heavy network traffic. With the booming of mobile cloud computing, users can access the service on demand with smart phones or other portable devices like iPad or Amazon kindle as well as PC. Our system provides virtual desktop web pages written in HTML/JavaScript to avoid frequent image transmissions and reduce network traffic. To build the cloud prototype system, we combine Lightweight TCP/IP stack (LwIP) and Java Optimized Processor (JOP) to build a web server enabling dynamic web page interactions. Our system significantly saves volumes of data in transmission and network bandwidth. Analytical performance evaluation shows that on average, our system suffers only 25% transmitting latency and saves 46% of energy efficiency in comparison to other solutions. Our efficient DaaS based on FPGA explores new application of embedded web server in green cloud computing as well as new service paradigm of mobile cloud computing.